2014
DOI: 10.1016/j.biomaterials.2014.04.083
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of chondroitinase-ABC, TGF-β1, and collagen crosslinking agent lysyl oxidase to engineer functional neotissues for fibrocartilage repair

Abstract: Patients suffering from damaged or diseased fibrocartilages currently have no effective long-term treatment options. Despite their potential, engineered tissues suffer from inferior biomechanical integrity and an inability to integrate in vivo. The present study identifies a treatment regimen (including the biophysical agent chondroitinase-ABC, the biochemical agent TGF-β1, and the collagen crosslinking agent lysyl oxidase) to prime highly cellularized, scaffold-free neofibrocartilage implants, effecting conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 43 publications
8
108
1
1
Order By: Relevance
“…The GAG content of minipig discs was low (1%/DW) in comparison to articular cartilage (30%/DW) 32 or knee meniscus (17%/DW) 33 ; similarly, low GAG content was found in human and FP discs. 13 The collagen/GAG ratio for the minipig disc was 28.9, which is more similar to humans (43.0) than FPs (67.3) (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The GAG content of minipig discs was low (1%/DW) in comparison to articular cartilage (30%/DW) 32 or knee meniscus (17%/DW) 33 ; similarly, low GAG content was found in human and FP discs. 13 The collagen/GAG ratio for the minipig disc was 28.9, which is more similar to humans (43.0) than FPs (67.3) (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the subcutaneous implantation of native-to-engineered cartilage assemblies pretreated with a two LOX applications and one C-ABC and TGF-b1 treatment increased interfacial Tensile modulus and ultimate tensile strength by 4.3-fold and 4.7-fold, respectively (Fig. 17) [82]. This study showed that LOX treatment primes the integration of highly cellularized and metabolically active neofibrocartilage, a promising approach to the significant obstacle of cartilage integration.…”
Section: Lox-mediated Enhancement Of Cartilage Integrationmentioning
confidence: 73%
“…These enhancements persisted at 12 weeks of culture. Collagen fibril diameter was also synergistically increased by 104% at 12 weeks [82].…”
Section: C-abc and Tgf-b1mentioning
confidence: 94%
“…В этом случае развитие новой ткани происходит лишь под действием гипоксии, факторов роста, связывающе-го агента лизилоксидазы и биомеханической сти-муляции, как правило, гидростатического давления [53][54][55][56][57].…”
Section: технологии стимулирования регенерации поврежденной хрящевunclassified